Burkitt’s Lymphoma of the Gastrohepatic Omentum: A Malignant Presentation of Pseudoachalasia - Eric Omar Then; Andrew Ofosu; Prashanth Rawla; Tagore Sunkara; Sriharsha Dadana; Andrea Culliford; Vinaya Gaduputi (Case Reports in Gastrointestinal Medicine)
Achalasia is an intrinsic disorder of the esophagus that results from loss of ganglion cells in the lower esophageal sphincter. Clinically it is manifested by dysphagia to solids and liquids, weight loss, regurgitation, and chest pain. Pseudoachalasia, in contrast, is a rare entity that causes identical symptoms, but has a divergent underlying pathogenesis. The symptomology in these cases oftentimes occurs secondary to extrinsic compression of the esophagus, mostly attributable to malignancy. Although many cases of extrinsic esophageal compression have been reported in the literature, rarely has this occurred secondary to Burkitt’s lymphoma in an adult. Here, we present a case of Burkitt’s lymphoma resulting in pseudoachalasia in a 70-year-old female. The concurrence of these two entities in one patient makes this case presentation especially rare.